Insomnia and circadian rhythm: a bibliometrics study and visualization analysis via CiteSpace - He, Qing-Yun; Dai, Ning; Mao, Meng; Ma, Jie; Wen, Qiao; Song, Dan-Dan; Liu, Yan; Li, Feng (Frontiers in Neurology, 2023)
Objective: This study aimed to use CiteSpace to analyze the status of insomnia and circadian rhythm, identify the hotspots and trends and provide a basis for the future study. Method: Web of Science was searched for studies in the field of insomnia and circadian from inception to April 14, 2023. CiteSpace was used to generate online maps of collaboration between countries and authors and revealed hot spots and frontiers in insomnia and circadian rhythm. Results: We searched 4696 publications related to insomnia and circadian rhythm. Bruno Etain had the most publications with 24 papers. USA and the University of California were the leading country and institution in this field, with 1672 and 269 papers, respectively. There was active cooperation between institutions, countries, and authors. Hot topics focused on circadian rhythm sleep disorders, circadian clock, light therapy, melatonin, and bipolar disorder. Conclusions: Based on the CiteSpace results, we recommend a more active collaboration between various countries, institutions, and authors to conduct clinical and basic research. Ongoing research focuses on the interaction of insomnia with circadian rhythms and the corresponding pathways of clock genes and, by extension, the role of circadian rhythms in disorders such as bipolar disorder. Modulation of circadian rhythms may be a hot spot for future insomnia therapies (such as light therapy and melatonin).